A VAR analysis for the uncovered interest parity and the ex-ante purchasing power parity: the role of macroeconomic and financial information - Corrado Macchiarelli (European Central Bank (ECB), 2011)
This study revisits the relation between the uncovered interest parity (UIP), the ex ante purchasing power parity (EXPPP) and the real interest parity (RIP) using a VAR approach for the US dollar, the British sterling and the Japanese yen interest rates, exchange rates and changes in prices. The original contribution is on developing some joint coefficient-based tests for the three parities conditions at a long horizon. Particularly, test results are derived by rewriting the UIP, the EXPPP and the RIP as a set of cross-equation restrictions in the VAR (see also Campbell and Shiller, 1987; Bekaert and Hodrick, 2001; and Bekaert et al., 2007; King and Kurmann, 2002). Consistent with the idea of some form of proportionality among the above three parities, we find a ”forward premium” bias in both the UIP - as it is normally found in empirical analysis (e.g. Fama, 1987) - and the ex ante PPP. The latter result is new in the literature and stems from testing the PPP in expectational terms, thus assuming agents to bear on the uncertainty of future exchange rate changes and inflation dynamics. The overall results confirm the UIP to be currency-based (see also Bekaert et al., 2007) and the EXPPP to be horizon-dependent (see also Lothian and Taylor, 1996; Taylor, 2002). Moreover, we find (weak) evidence that conditioning the VAR on variables having a strong forward-looking component (i.e. share prices) helps recover a unitary coefficient in the UIP equation.
Keywords: E31; E43; E44; F31; C58; 330; international parity conditions; PPP; RIP; UIP